(untitled) (Journal of Medical Sciences, 2025)
Objectives: This study was designed to evaluate the adhesion of different root canal sealers (TotalFill BC, AH Plus and MTA Fillapex) to human root dentin treated with different types of intracanal medicaments (CHX gel & Ca(OH)2 paste), using the push-out test. Materials and methods: One hundred and thirty five extracted single-rooted human teeth were prepared using protaper rotary files instruments up to size #F4. The specimens were divided into three groups according to the medication used (CHX gel, Ca(OH)2 and control). Each group was subdivided into three subgroups according to the sealer used for obturation (TotalFill BC, AH Plus, and MTA Fillapex). The obturated roots were cut perpendicular to the long axis to create 2-mm thickness of slices, from the apical, middle and coronal thirds then subjected to push-out test at a crosshead- speed of 0.5mm/min to record the maximum failure load.. Results: Regardless of the type of intracanal medication used TotalFill BC sealer & MTA Fillapex sealer showed the highest and lowest bond strength respectively. The use or absence of medication did not statically affect dislodgment resistance of root canal filling. Conclusion: Prior application of CHX gel or Ca(OH)2 paste did not significantly affect the adhesion of Total Fill BC, AH Plus and MTA Fillapex Sealers